METHODS OF TEACHING ENGLISH IN DIFFERENT LEARNING STYLES - Z. M. Tukhtasinova; A. B. Myssekeyeva (Galaxy International Interdisciplinary Research Journal, 2024)
This article is devoted to the study of the methods of teaching English in different learning styles. Mainly, it discusses the importance, use of VAK (visual, auditory, kinaesthetic) and VARK (visual, auditory, kinaesthetic, reading/writing preference) models in teaching English as a foreign language.